Aging envisage imbalance of the periodontium: A keystone in oral disease and systemic health - Villalobos, Verónica; Garrido, Mauricio; Reyes, Antonia; Fernández, Christian; Diaz, Catalina; Torres, Vicente A.; González, Pablo A.; Cáceres, Mónica (Frontiers in Immunology, 2022)
Aging is a gradual and progressive deterioration of integrity across multiple organ systems that negatively affects gingival wound healing. The cellular responses associated with wound healing, such as collagen synthesis, cell migration, proliferation, and collagen contraction, have been shown to be lower in gingival fibroblasts (the most abundant cells from the connective gingival tissue) in aged donors than young donors. Cellular senescence is one of the hallmarks of aging, which is characterized by the acquisition of a senescence-associated secretory phenotype that is characterized by the release of pro-inflammatory cytokines, chemokines, growth factors, and proteases which have been implicated in the recruitment of immune cells such as neutrophils, T cells and monocytes. Moreover, during aging, macrophages show altered acquisition of functional phenotypes in response to the tissue microenvironment. Thus, inflammatory and resolution macrophage-mediated processes are impaired, impacting the progression of periodontal disease. Interestingly, salivary antimicrobial peptides, such as histatins, which are involved in various functions, such as antifungal, bactericidal, enamel-protecting, angiogenesis, and re-epithelization, have been shown to fluctuate with aging. Several studies have associated the presence of Porphyromonas gingivalis, a key pathogen related to periodontitis and apical periodontitis, with the progression of Alzheimer’s disease (AD), as well as gut, esophageal, and gastric cancers. Moreover, herpes simplex virus types 1 and 2 have been associated with the severity of periodontal disease, cardiovascular complications, and nervous system-related pathologies. This review encompasses the effects of aging on periodontal tissues, how P. gingivalis and HSV infections could favor periodontitis and their relationship with other pathologies.